Chronic contact allergic and irritant dermatitis of palms and soles - Jovanović, Dragan L. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Objective: Chronic contact allergic dermatitis (CAD) and contact irritant dermatitis (CID) of palms and soles have similar clinical features. The pathohistological characteristics of chronic palmoplantar CAD and CID are alsosimilar, as presented by hyperkeratosis, acanthosis, and a chronic inflammatory infiltrate in dermis. The aim of our study was to reconsider whether it makes sense to order pathohistological investigations in the differential diagnosis of chronic palmoplantar CAD and CID. Materials and methods: Biopsies of palmoplantar skin lesions in 24 patients with CAD and 24 with CID were examined according to routine pathohistology. Hematoxylin-eosin and periodic-acid-Schiff (PAS) staining were used. Results: The inflammatory infiltrate in papillary dermis was more marked in CAD, and often composed of eosinophils and lymphocytes. In CID the infiltrate was less pronounced and composed of lymphocytes. Hyperkeratosis is characteristic of both diseases. Even though all examined lesions were chronic, spongiosis, microvesicles and their sequels were seen in the epidermis more often in CAD. Conclusion: Pathohistological findings in chronic palmoplantar CAD and CID must be considered together with results of clinical examination and other tests. Though some slight differences were noticed, the value of light microscopic examination in order to differentiate between chronic CAD and CID is limited.
Keywords: Biopsija; Biopsy; dermatitis; Dermatitis alergijski, kontaktni; Dermatitis iritantni; Dermatitis, Allergic Contact; Dermatitis, Irritant; dermatologija; Diagnosis; kožne bolezni; Pathology